Validation of a DNA biochip for species identification in food forensic science. (August 2017) - Beltramo, Chiara; Riina, Maria Vittoria; Colussi, Silvia; Campia, Valentina; Maniaci, Maria Grazia; Biolatti, Cristina; Trisorio, Silvia; Modesto, Paola; Peletto, Simone; Acutis, Pier Luigi
Abstract: Authentication of food product ingredients by food control agencies relies on analytical laboratory methods for animal species identification. Such methods must be validated if their results are to be used as acceptable evidence in a court of law. Following the validation guidelines of the Scientific Working Group on DNA Analysis Methods (SWGDAM), we carried out a validation process for the Low Cost and Density (LCD) Array (MEAT 5.0 version) kit for food forensics based on a DNA biochip technology that simultaneously detects 24 animal species. Mixtures of the animal species the kit is designed to detect were prepared at different concentrations and tested on raw/pasteurized, and heated meat and milk matrices. The LCD Array showed high specificity and high sensitivity and it appeared to be robust and repeatable. As such, it provides a useful tool for detecting common adulterants in food items of animal origin. Highlights: Performance evaluation of LCD Array kit for forensic science to detect food fraud. Validation following Scientific Working Group on DNA Analysis Methods guidelines. High specificity and sensitivity of the kit both for meat and milk matrices. Satisfactory performance also on processed food. Good performance also for processed food.